Estimation the Prevalence of Anemia in Pregnancy in Tuz City, Saladin Governorate - Hassan Y. Hassan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Anemia is a state of decreased level of hemoglobin below normal. WHO defines anemia as hemoglobin level below 10.5 gm/dl in 2nd trimester, below 11 gm / dl in 1st and 2nd trimesters and below 10gm/dl postpartum. The Aim of this study to estimate prevalence of anemia in pregnancy in Tuz city, Saladin governorate. Subjects and Methods:This study was conducted at the beginning of November 2019 to the end of February 2020. 150 women at child bearing age were participated in this study (100 pregnant women collected randomly from those attending antenatal care center in Tuz General Hospital in Saladin governorate and 50 healthy non pregnant women collected randomly as control.). Written consent was taken from each woman participating in the study after expanding the aim of the study for each subject. In the laboratory of the hospital, 3 ml of cubital venous blood had been drawn from each patient using disposable syringes and needles.The same automated analyzer had been used to perform complete blood count (CBC) and 5 parameters had been estimated for each patient. Results: 96% of non-pregnant women had normal hemoglobin level and 4%of them had mild to moderate anemia. Among pregnant women, 4% of them severe anemia, 65% of them had mild to moderate anemia, and 31% of them had normal hemoglobin level. Among pregnant women in 1st trimester, 27.8% of them had mild to moderate anemia and 72.2% of them had normal hemoglobin level. Among pregnant women in 2nd trimester, 8,3% of them had severe anemia, 75% had mild to moderate anemia, 16,7% of them had normal hemoglobin level. Among pregnant women in 3rd trimester, 2,2% had severe anemia, 71,7% had mild to moderate anemia and 26,1% had normal hemoglobin level.